2018
DOI: 10.3855/jidc.10473
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic bacteriological profile and antimicrobial susceptibility pattern of pus isolates from tertiary care hospital in India

Abstract: Introduction: Pyogenic infections are an important cause of sepsis. These infections are difficult to treat because of the pathogens with increasing antibiotic resistance. It is important to know the pathogens causing the infections and its antibiotic susceptibility for proper management of the patients. Methodology: A retrospective analysis of 1428 culture positive pus and tissue samples received in the department of microbiology from various departments in the hospital between January 2012 to 2017 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
2
6
1
Order By: Relevance
“…In the present study, monomicrobial infections predominated (90.19%), while polymicrobial infections were observed (9.80%) ( Tables 3 and 4 ). The study by Sudhaharan et al 11 found that monomicrobial infection was 93.2% and polymicrobial infection was 6.8%; this result is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, monomicrobial infections predominated (90.19%), while polymicrobial infections were observed (9.80%) ( Tables 3 and 4 ). The study by Sudhaharan et al 11 found that monomicrobial infection was 93.2% and polymicrobial infection was 6.8%; this result is consistent with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…10 The loss of skin integrity due to a variety of reasons creates an environment conducive to the colonization and proliferation of microorganisms. 11 Humidity, heat, and nutrition in the wound attract pathogen from the cutaneous surface, environment, or the patient's own flora, which grow and release various virulence factors, resulting in wound infection. 12 Immune cells are recruited to the infection site by the body's defense mechanism to fight pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…23 A study in South India between January 2012 and 2017 shows B. pseudomallei as a rare pathogen in only three pus specimens. 24 Thus, the current study shows the emergence of B. pseudomallei as a significant pathogen in localized pyogenic infections in eastern India, distributed in various districts of Odisha and West Bengal. The apparent concentration of maximum number of cases in Khordha district may be because our hospital is situated in Khordha district of Odisha, and hence the likelihood of concentration of more cases in Khordha district.…”
Section: Discussionmentioning
confidence: 60%
“…27 The antibiotic susceptibility patterns of all isolates were studied. The antibiotic panel for Gram positive cocci, Gram 28 However, the Gram positive cocci were resistant to commonly used antibiotics like amoxicillin with clavulanic acid, ciprofloxacin and pencillin. This difference could be due to better hospital infection control practices followed in our hospital.…”
Section: Discussionmentioning
confidence: 99%